Parental and peer support, intrinsic motivation, and volleyball interest among female junior high students - Randy Syafrima; Muhamad Sazeli Rifki; Arsil Arsil; Sepriadi Sepriadi (Jurnal SPORTIF : Jurnal Penelitian Pembelajaran, 2026)
Participation in school-based sports and extracurricular activities among female students remains relatively low and is often influenced by social support and internal motivational factors. This study examined the influence of parental and peer support on female students' interest in engaging in school-based volleyball extracurricular activities, with intrinsic motivation as a potential mediating variable. A quantitative correlational design using path analysis was employed. The participants were female students actively involved in volleyball extracurricular programs at a public junior high school in Padang (SMP Negeri 41 Padang). Data were collected using validated and reliable Likert-scale questionnaires. The results showed that parental support (β = 0.42, p < 0.001) and peer support (β = 0.36, p = 0.002) significantly predicted intrinsic motivation, which, in turn, significantly predicted students' interest in participating in volleyball (β = 0.51, p < 0.001). Intrinsic motivation was suggested to function as a mediating variable, indicating that social support influences students' interest both directly and indirectly. Parental support, peer support, and intrinsic motivation jointly accounted for 62.5% of the variance in students' interest, while other factors influenced the remaining 37.5%. These findings highlight the importance of social support and intrinsic motivation in promoting sustained participation in school-based sports and extracurricular activities.